PAREMIOLOGY AS A SCIENCE (Scientific journal of the Fergana State University, 2024)
This article discusses the paremiology, its history and usage in different times. Scientists study the field of Proverbs and sayings called paremiology. Paremia is a Greek word for " deep meaning sentence, hrase,proverb, saying". Paremia is a phenomenon of stability, and implies a whole content, a semantic whole means.Paremiology is an observation of the laws of the universe, life  representing conclusions drawn based on reliance on his experiments, people's attitude to society, state of mind, ethnic and aesthetic feelings, embodied positive qualities, oral speech moving in shape from generation to generation, compact and simple, short and meaningful logic proverb, saying, aphorism which appeared in the generalization.